Emotion dysregulation, temperamental vulnerability, and parental depression in adolescents: Correspondence between physiological and informant-report measures. (August 2019) - Van Beveren, Marie-Lotte; Mueller, Sven C.; Braet, Caroline
Abstract: Although numerous studies reveal altered respiratory sinus arrhythmia (RSA) among children, adolescents, and adults who exhibit emotion dysregulation, effects of temperamental vulnerability and parental mental health on RSA remain unclear. We evaluated the relationship among emotion regulation, RSA, and RSA reactivity in a pooled sample of 24 vulnerable and 31 resilient adolescents (mean age = 13.69 years; 60% girls), including associations with temperamental vulnerability and parental depressive symptoms. Participants watched a neutral film clip while their resting RSA was recorded, and then completed a reward and frustration task, using an affective Posner paradigm. Temperament and emotion regulation were assessed via self-report and parent report, and parents reported on their own depressive symptoms. Low resting RSA was associated with temperamental negative emotionality, whereas greater RSA reactivity to frustration was associated with maladaptive emotion regulation strategies. No significant relations were found between RSA and parental depressive symptoms. This study elucidates the role of RSA as a biomarker of individual differences in emotion dysregulation and temperamental vulnerability and stresses the importance of considering multiple units of analyses, as well as functional domains, when studying emotional responding and regulation in adolescents.